Performance of sustainable ternary blended concrete using rice husk ash and metakaolin as partial cement substitutes - Hasan, Kamrul; Khatun, Humaira; Mazumder, Roni; Putra Jaya, Ramadhansyah; Fadzil, Mat Yahaya (Springer, 2025)
The depletion of natural resources, high carbon dioxide (CO2) emissions, and rising cement production costs have raised global concerns. Consequently, there is growing interest in exploring alternative materials that can reduce both the environmental impact, and the cost associated with cement production. This study investigates the performance of sustainable ternary blended concrete (STBC) incorporating 0–30% rice husk ash (RHA) and metakaolin (MK) as partial replacements for cement. It evaluates the physical and chemical properties, morphological characteristics, and both experimental and statistical analyses of the fresh, hardened, and durable properties of STBC. Additionally, the study examines CO2 emissions and overall costs, aiming to promote more sustainable production practices. The results showed that the inclusion of RHA and MK reduced the workability of STBC. However, a 20% RHA + MK blend achieved the highest compressive strength, with a 47.22% increase compared to the control mix. It also exhibited the lowest water absorption, with a reduction of 45.65%. Furthermore, the inclusion of RHA and MK decreased both internal and external heat of hydration and delayed the onset of corrosion. Moreover, a 10% replacement level also demonstrated acceptable performance. On the other hand, a 30% RHA + MK blend reduced CO2 emissions by 10% and costs by 13.77% compared to traditional cement. Therefore, incorporating RHA and MK offers an effective method for utilizing these industrial by-products while enhancing the sustainability of construction practices. This approach enables the concrete industry to contribute to resource conservation, waste reduction, and broader sustainable development goals.